(3TQM GdCfaGS GdQhMGfjIs - (3eMeO Hf YHO Gdedc GdOjdeis; (3CMeO Hf YWGA Gddg GdScfOQj, CHh GdYHGSs
(3ChdgG (B:s
(3GdMeO ddg GdPi dGcja dcjag hdG TF deKdg CeG HYO aEf gPG TQM cJGH GdCfaGS GdJi LeYgG GdEeGeGf CHh GdbGSe LfjO Hf eMeO hCHh GdYHGS CMeO Hf YWGA Gddg ai gPG GdcJGH eG UM hKHJ YfOgeG s
(3BNQgG (B:s
(3hLYd GdCKQ hGdKeQ JaSjQ GddeKQ GdeDKQ Jage Ef TGA Gddg hMOg JeJ gPg GdcdeGJ GdeLehYI ai cJGH GdCfaGS HJaGSjQ aSQJgG Ydi haGb ePGgHge hGdd GdeSJYGf hYdjg GdJcdGf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJhMjO hGdedd hGdfMds